Correlação entre inteligência emocional, suporte social e dependência emocional em relacionamentos amorosos no Brasil - Lima, Victória Assis (Universidade Federal de São Carlos, 2025)
Emotional intelligence (EI) has been extensively studied as a crucial factor for psychological well-being and interpersonal success. EI is associated with various areas of life, including the quality of romantic relationships, significantly influencing these bonds. However, some of these relationships can be dysfunctional and harmful to the individuals involved, especially when there is emotional dependency (ED). ED is characterized by a pattern of behaviors and beliefs centered on the intimate partner, leaving the emotionally dependent individual vulnerable to psychological distress, violence, and suicide attempts. Although EI may potentially act as a protective factor against ED, research on this correlation is still scarce in Brazil. Furthermore, stressful and vulnerable situations can be mitigated with quality social support (SS) from networks of friends, family, or other social groups. Thus, it is hypothesized that individuals with greater development of emotional intelligence and who perceive quality social support have less emotional dependency. In this context, the present study seeks to explore the relationship between EI, ED, and SS. The objective is to investigate the relationship between emotional intelligence, emotional dependency, and social support in people who are in romantic relationships in Brazil. The project will use a quantitative approach, employing instruments to assess emotional intelligence (TOHE, QoRE, QoE), emotional dependency (CDE), and social support (EPSUS-A) in a diverse sample of adults who are in romantic relationships. It is expected that the results found here can serve as a reference for the development of future psychological interventions and treatments in the management of emotional dependency.
Correlation between emotional intelligence, social support, and emotional dependence in romantic relationships in Brazil
Keywords: inteligência emocional; dependência emocional; suporte social; avaliação psicológica; relacionamentos; CIENCIAS HUMANAS::PSICOLOGIA::FUNDAMENTOS E MEDIDAS DA PSICOLOGIA::CONSTRUCAO E VALIDADE DE TESTES, ESCALAS E OUTRAS MEDIDAS PSICOLOGICAS; 3. Saúde e Bem-Estar